Fossil woods with coniferalean affinities from the Upper Cretaceous (Campanian–Maastrichtian) Puntudo Chico Formation, Chubut Province, Argentina - Vera, Ezequiel Ignacio; Perez Loinaze, Valeria Susana; Llorens, Magdalena; Páez, Manuel Antonio; Passalia, Mauro Gabriel (Cretaceous Research)
The Puntudo Chico Formation is a continental sequence overlying the Chubut Group at the central-East of the Cañadón Asfalto Basin in Patagonia (Chubut Province, Argentina). The age of this unit, Campanian–Maastrichtian, makes it comparable with other Patagonian units, such as the Allen (Río Negro Province) and La Colonia Formation (Chubut Province), well-known by their paleontological content, including plants, mammals, and non-avian dinosaurs. Contrasting, the Puntudo Chico Formation fossil content is almost unknown, and even if fossil woods were reported, detailed studies were lacking. In this contribution, fossil woods collected from the Puntudo Chico Formation are studied, and three different conifer taxa are identified: Podocarpoxylon mazzonii (Petriella) Müller-Stoll & J. Schultze-Motel 1990, Brachyoxylon sp. cf. B. currumilii Bodnar, Escapa, Cúneo & Gnaedinger, 2013, and Agathoxylon antarcticus (Poole et Cantrill) Pujana, Santillana & Marenssi, 2014. This flora seems to be part of a distinctive Late Cretaceous–Danian floristic assemblages that inhabited a warm region located approximately at 38–42°S, that were probably linked and somewhat nearby the Kawas Sea, an inland sea that flooded the Neuquén and Río Colorado basins during the first Atlantic Transgressive Event in Patagonia. Fil: Vera, Ezequiel Ignacio. Consejo Nacional de Investigaciones Científicas y Técnicas. Oficina de Coordinación Administrativa Parque Centenario. Museo Argentino de Ciencias Naturales "Bernardino Rivadavia"; Argentina. Universidad de Buenos Aires. Facultad de Ciencias Exactas y Naturales. Departamento de Geología; Argentina Fil: Perez Loinaze, Valeria Susana. Consejo Nacional de Investigaciones Científicas y Técnicas. Oficina de Coordinación Administrativa Parque Centenario. Museo Argentino de Ciencias Naturales "Bernardino Rivadavia"; Argentina. Universidad Nacional de la Patagonia "San Juan Bosco"; Argentina Fil: Llorens, Magdalena. Consejo Nacional de Investigaciones Científicas y Técnicas; Argentina. ...